Socialization of Improving the Quality of Public Services Through Digital-Based Integrated Village Governance in Villages - Prilosadoso, Basnendar Herry; Salampessy, Maryam; Yahya, Afif Syarifudin; Afrizal, Dedy; Mado, Yohanes Jibrail (Universitas Pahlawan Tuanku Tambusai, 2024)
The three villages that were the objects of observation and the author carried out community service within a period of two weeks to one month had the same problem, namely regarding the quality of public services that were still minimal. The author took the initiative to conduct socialization to village officials to improve the quality of public services. During the service for a period of two weeks to one month, the author has a realistic target, namely that village officials can master the internet. In the first week and part of the second week, the author conducted socialization on how to use technology properly, the author taught basic things until the village officials could operate the technology they had. In the final stage, the author recruited stakeholders to create websites for the three villages above so that they could serve the rural community digitally. The author would like to express his deepest gratitude to a number of parties involved in the making of the article and the author's dedication to the villages of Baraya and Babatan that have been mentioned since the introduction. The author would like to express his deepest gratitude to the Village Head, Mr. Somad and Mr. Sugeng for the direction given and other village officials who cannot be mentioned one by one